Unravelling seismogenesis and characterizing the unique features of two significant felt earthquakes (M > 4.0) of 2020 in the southwestern parts of the Delhi region - Prajapati, Sanjay K.; Pandey, Ajeet P.; Bhattacharjee, Sudipto; Vashisth, Shikha; Mishra, O. P. (Frontiers in Earth Science, 2024)
Two significant earthquakes (M 4.6 and 4.2) occurred close to a NE-SW trending lineament in the southwestern part of Delhi NCR (National Capital Region) within a short time span of about five months in 2020. These events were located to the north of the Alwar district of Rajasthan that generated a significant ground shaking in and around Delhi region. In the present study, an effort was made to understand a causal relationship between the events and a nearby source in the region, geologically demarcated as lineament. We analysed the broadband waveform data of 26 seismic stations that recorded the recent events of July 03, 2020 (M4.6) and December 17, 2020 (M4.2). Typically, the epicentral area has been devoid of significant earthquakes since past six decades; however, a few minor events (M < 4.0) have been recorded. Analysis of earthquakes database for two decades (2000-2020) revealed low seismicity (nearly quiescent like situation) in ~100 sq km area around the epicentral zone, unlike considerable seismicity along faults/lineaments close to the Delhi region. The full-waveform inversion analyses of events indicate normal faulting with minor strike-slip component. The source parameters, viz., source radius, stress drop, and seismic moment were estimated to be 6 km, 166 bars, and 8.28E+15 Nm, respectively for the July 03, 2020 event and 4 km, 138 bars, and 2.29E+15 Nm, respectively for December 17, 2020 event. The causative source of these events is ascertained based on the stress inversion modelling that indicates a NW-SE tensile stress corroborating well with the NE-SW trending lineament mapped in the study region. The static Coulomb stress modelling indicates that event occurred on July 3, 2020 had advanced the triggering process of the event in the northeast segment of same source that occurred on December 17, 2020. We also emphasize that the aforementioned lineament probably activated due to the regional tectonics of the study area. The causative source of these events with strike 48°, dip 86°, rake − 60° is found to be in conformity with the local tectonics and is well supplemented by a high-stress ratio (0.70 ± 0.05) and low friction coefficient (0.5).